Genetic Variation Determines PPARγ Function and Antidiabetic Drug Response In Vivo - Soccio, Raymond E. (Cell, 2015)
SNPs affecting disease risk often reside in non-coding genomic regions. Here we show that SNPs are highly enriched at mouse strain-selective adipose tissue binding sites for PPARγ, a nuclear receptor for antidiabetic drugs. Many such SNPs alter binding motifs for PPARγ or cooperating factors, and functionally regulate nearby genes whose expression is strain-selective and imbalanced in heterozygous F1 mice. Moreover, genetically-determined binding of PPARγ accounts for mouse strain-specific transcriptional effects of TZD drugs, providing proof-of-concept for personalized medicine related to nuclear receptor genomic occupancy. In human fat, motif-altering SNPs cause differential PPARγ binding, provide a molecular mechanism for some expression quantitative trait loci, and are risk factors for dysmetabolic traits in genome-wide association studies. One PPARγ motif-altering SNP is associated with HDL levels and other metabolic syndrome parameters. Thus, natural genetic variation in PPARγ genomic occupancy determines individual disease risk and drug response.